2016
DOI: 10.1038/srep33866
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation of the Himalayas as revealed by arc-parallel gravity anomalies

Abstract: Lateral variations along the Himalayan arc are suggested by an increasing number of studies and carry important information about the orogen’s segmentation. Here we compile the hitherto most complete land gravity dataset in the region which enables the currently highest resolution plausible analysis. To study lateral variations in collisional structure we compute arc-parallel gravity anomalies (APaGA) by subtracting the average arc-perpendicular profile from our dataset; we compute likewise for topography (APa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 39 publications
6
80
0
Order By: Relevance
“…In Western Nepal, the distance over which the Moho reaches its maximum depth differs from Central Nepal (Figure ; Nábělek et al, ): The gentler descent ends further north, north of the Higher Himalaya, at nearly 80‐km depth beneath southern Tibet (Xu et al, ). This may reflect a slightly different flexural rigidity of the India plate in Western Nepal compared to Central Nepal, although there is no significant difference in flexure West and East of our profile in Nepal as seen by gravity anomalies and numerical modeling (Berthet et al, ), unlike further toward NW India and to the Eastern Himalaya (Hammer et al, ; Hetényi, Cattin, et al, ; Lyon‐Caen & Molnar, ).…”
Section: Interpretation and Discussionmentioning
confidence: 77%
“…In Western Nepal, the distance over which the Moho reaches its maximum depth differs from Central Nepal (Figure ; Nábělek et al, ): The gentler descent ends further north, north of the Higher Himalaya, at nearly 80‐km depth beneath southern Tibet (Xu et al, ). This may reflect a slightly different flexural rigidity of the India plate in Western Nepal compared to Central Nepal, although there is no significant difference in flexure West and East of our profile in Nepal as seen by gravity anomalies and numerical modeling (Berthet et al, ), unlike further toward NW India and to the Eastern Himalaya (Hammer et al, ; Hetényi, Cattin, et al, ; Lyon‐Caen & Molnar, ).…”
Section: Interpretation and Discussionmentioning
confidence: 77%
“…Underthrusting bathymetric features like the DHR (Figure ) can change the crustal configuration and geometry of the MHT as observed in this study. Lateral segmentation of subsurface structures in the Himalaya is revealed by arc‐parallel gravity anomaly [ Hetényi et al , ]. The seismicity pattern in the HSB in Satluj valley and in the adjacent Garhwal Himalaya clearly reflects the role of the ramp structure on the MHT in the generation of clustered seismicity [ Caldwell et al , ].…”
Section: Discussionmentioning
confidence: 81%
“…Significant along‐strike variations in topography and relief [ Duncan et al , ], convergence and shortening rates [ Banerjee and Bürgmann , ; Paul et al , ], and exhumation rates [ Robert et al , ] are also reported. Recent high resolution gravity data also reveal lateral segmentation of subsurface structure in the Himalaya [ Hetényi et al , ]. Seismicity studies suggest along‐strike variation in the northwest Himalaya [e.g., Gahalaut and Kalpna , ; Arora et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the characteristics (rupture geometry and intensity attenuation) of a given M ~ 8 earthquake may naturally deviate from statistically determined averages, our results seem not to contradict any known observation and seem to be credible for this 300 year old event. The along‐arc location and potential extent of the earthquake also conforms to the segmentation of the Himalayas as revealed by arc‐parallel gravity anomalies [ Hetényi et al ., ].…”
Section: Results and Interpretationmentioning
confidence: 99%